BUILDING AUDIENCE ENGAGEMENT THROUGH VISUAL STORYTELLING: A Study Of The “Ujung Jalan” Segment On The Masrang Youtube Channel - Mujahid, Muhammad Widzar; Rahmawati, Yulia; Setiawati, Titin (The Indonesian Journal of Social Studies, 2025)
This study aims to examine the visual storytelling strategy implemented in the Ujung Jalan segment of the Masrang YouTube channel. Using an organizational communication framework, the research explores how creative processes and communication decisions are shaped through interactions between the channel’s creator and two collaborators involved in content production. Employing a qualitative approach through in-depth interviews, the findings reveal that the use of quiet, slow-paced, and narration-free visuals is a deliberate strategy designed to differentiate Masrang from typical travel vlogs. This strategy goes beyond delivering information; it also creates a reflective emotional space for the audience. The results show that Masrang operates through a collaborative communication model resembling a micro-organizational structure, where content is developed through idea exchange, role coordination, and shared objectives. As such, Masrang serves as an example of how organizational communication can be applied within independent content creation rooted in a creative community.